2020
DOI: 10.3389/fonc.2020.00454
|View full text |Cite
|
Sign up to set email alerts
|

Breast Adipocyte Co-culture Increases the Expression of Pro-angiogenic Factors in Macrophages

Abstract: Obese individuals with breast cancer have a poorer prognosis and higher risk of metastatic disease vs. non-obese patients. Adipose tissue in obese individuals is characterized by an enhanced macrophage infiltration, creating a microenvironment that favors tumor progression. Here, we demonstrate a role for adipocyte-macrophage interactions in the regulation of angiogenesis. Co-culture of THP-1 macrophages with human breast adipocytes led to increased expression of the pro-angiogenic growth factor, vascular endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Several adipokines including leptin, IL-6, and TNF-α are capable of increasing VEGFA expression in THP-1 macrophages co-cultured with adipocytes. Compared with THP-1 cells cultured alone, the medium of THP-1 cells previously exposed to human adipocytes stimulated endothelial tube formation more significantly [ 102 ]. Therefore, revealing the underlying mechanisms of adipocyte-driven immune cells and immune cascades is necessary to understand the role of adipokines in TME.…”
Section: Adipocytes and Breast Cancermentioning
confidence: 99%
“…Several adipokines including leptin, IL-6, and TNF-α are capable of increasing VEGFA expression in THP-1 macrophages co-cultured with adipocytes. Compared with THP-1 cells cultured alone, the medium of THP-1 cells previously exposed to human adipocytes stimulated endothelial tube formation more significantly [ 102 ]. Therefore, revealing the underlying mechanisms of adipocyte-driven immune cells and immune cascades is necessary to understand the role of adipokines in TME.…”
Section: Adipocytes and Breast Cancermentioning
confidence: 99%
“…The loss of adipocyte specification and necrosis directly activated macrophages and thus enhanced the inflammation state in TME. The combination of soluble breast adipocyte-derived leptin, insulin, IL-6, and TNF-α were inducers of the release of angiogenic mediators in macrophages, representing a potential mechanism for the enhanced risk of breast cancer progression in obese individuals [ 116 ]. Yadav et al indicated that some adipocyte-derived mediators, such as leptin, insulin, IL-6, and TNF-α, could facilitate VEGF content in THP-1 macrophages in co-culture model.…”
Section: Adipocyte Secretome In Regulating Immune Cells In Breast Cancermentioning
confidence: 99%
“…Insulin can act synergistically with inflammation to promote BC growth and metastasis (58). Insulin could increase the expression of VEGFA in macrophages and have proangiogenic effects in vitro endothelial tube formation assay (33). Rabin-Court et al validated that the obesity-driven elevated insulin could upregulate mitochondrial glucose oxidation in obesity-associated tumor cell lines (BC, colon cancer, and prostate cancer cells) correlated with a dosedependent increase in cell division (59).…”
Section: Insulin and Igfmentioning
confidence: 99%